IMPLIKASI KOMPONEN PERUBAHAN PAJAK DALAM LABATERHADAP PERSISTENSI DAN PERAMALAN STUDI TERHADAP PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2010-2013 - Sari, Dewi Kartika; Anggraeni, Birawani Dwi; Aulia, Sandra (UI Scholars Hub, 2016)
This research aims to determine the implications of the tax change component in the income tax to the persistence and forecasting of future earnings, and also comparing the effect of tax changes component in initial earning with the tax change component in revised earnings, in order to know which are more persistent. Using all companies listed in Indonesia Stock Exchange during the year 2010-2013 as the samples, this research showed that the tax change component in income tax empirically proven to have a persistent effect on future earnings. And compared with tax change component in initial earnings, value of tax change component in revised earnings are better and persistent in forecast earnings.